2007
DOI: 10.1111/j.1365-2222.2007.02886.x
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell and allergic diseases: role in pathogenesis and implications for therapy

Abstract: SummaryMast cells have long been recognized for their role in the genesis of allergic inflammation; and more recently for their participation in innate and acquired immune responses. Mast cells reside within tissues including the skin and mucosal membranes, which interface with the external environment; as well as being found within vascularized tissues next to nerves, blood vessels and glandular structures. Mast cells have the capability of reacting both within minutes and over hours to specific stimuli, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
186
1
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 165 publications
(178 reference statements)
2
186
1
13
Order By: Relevance
“…Mast cells have been implicated in airway inflammation and remodeling [24,26], but long-term smoking (4 mo) did not show enhanced numbers of mast cells in OVA-induced lung tissues in vivo [13]. In contrast to these findings, we observed that smoke elevated the numbers of mast cells in BAL cells and lung tissues of OVA/S mice, although both studies differed in various factors such as smoke exposed periods and allergen challenge.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Mast cells have been implicated in airway inflammation and remodeling [24,26], but long-term smoking (4 mo) did not show enhanced numbers of mast cells in OVA-induced lung tissues in vivo [13]. In contrast to these findings, we observed that smoke elevated the numbers of mast cells in BAL cells and lung tissues of OVA/S mice, although both studies differed in various factors such as smoke exposed periods and allergen challenge.…”
Section: Discussioncontrasting
confidence: 77%
“…Mast cells are activated by cross-linking of antigen-specific IgE bound to the high-affinity receptor (FcεRI) on their membranes. Activated mast cells secrete preformed mediators (histamine, tryptase, chymase, TNFα, and other proteins) as well as newly synthesized proinflammatory mediators such as PGD2, leukotrienes, cytokines, and chemokines [24]. These mediators contribute to airway inflammation and remodeling in allergic asthma [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells in the lower airways contribute to the development of asthma and allergic diseases (26). Mast cells are of interest because of a possible relation between chorioamnionitis, preterm birth, and the development of asthma later in life (27,28).…”
Section: Effects Of Lps As Gestation Advancesmentioning
confidence: 99%
“…It has been shown that increased expression of the T-helper cell (Th)2-cytokines interleukin (IL)-4 and IL-13 not only promotes eosinophilic inflammation, but also activates mast cells [6], and that microlocalisation of these mast cells predominantly in the ASM layer is a key factor in the pathophysiology of asthma [7]. Activated mast cells release various mediators, which can lead to enhanced ASM contraction and proliferation [6,8]. Interestingly, gene expression analysis has shown that the degree of Th2-cytokine expression in bronchial biopsies varies between asthma patients, being associated with aspects of airway remodelling and responsiveness to inhaled steroids [9].…”
Section: Introductionmentioning
confidence: 99%